ManagemOnt: A Semantic Approach to Software Engineering Management Process - Ulu, Baris; Diri, Banu (SPRINGER-VERLAG BERLIN, 2009)
Software engineering processes, today, tend to have a gap between the assets because of non-managable experiences in the domain which causes the organizations to fail in process improvement activities and software engineering practices in terms of time and cost. The data maintained in current software engineering process models, such as project and resource plans, documents, metrics, etc. is syntactic and out of interpretation. The lack of interpretation results in redundant data for an asset of software engineering process. It is well-known for years that each asset in software engineering domain generates an output which is an input for another asset in the domain in a logically related manner. This approach to software engineering process assets reveals knowledge-based software engineering process modeling via inference and reuse of domain experiences. It is proposed to model semantic software engineering process and their assets by means of ontologies to achieve the inference and reuse of domain knowledge in a way different from syntactic approach. In order to trigger semantic software engineering processes, project planning activity is prototyped from software engineering management process since this activity almost comprises the mentioned process data because of its position in software engineering processes and practices.
Keywords: Ontological software engineering management; semantic software engineering management; Computer Science; Information Science & Library Science